2012
DOI: 10.1007/s11604-012-0122-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined intra-arterial infusion and systemic chemoradiotherapy for stage IV squamous cell carcinoma of the mandibular gingiva

Abstract: Combined intra-arterial infusion and systemic chemoradiotherapy may be an effective treatment for patients with stage IV mandibular gingival cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For CIS, the first dose consisted of 5 mg/kg and the second 2.5 mg/kg (Havelka, Berndtsson, Olofsson, Shoshan, & Linder, ). These doses were a proportional adaptation to rats from the protocol used for cancer treatment in humans, which is determined by body surface (FDA; Nakasato et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For CIS, the first dose consisted of 5 mg/kg and the second 2.5 mg/kg (Havelka, Berndtsson, Olofsson, Shoshan, & Linder, ). These doses were a proportional adaptation to rats from the protocol used for cancer treatment in humans, which is determined by body surface (FDA; Nakasato et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…I G U R E 1 Clinical images showing the exposure of the tibial metaphysis (a), the drilled alveolus (b), the implant insertion (c) and bicortical fixation of the implant with sufficient amount of bone at the site (d) , which is determined by body surface (FDA;Nakasato et al, 2012).…”
mentioning
confidence: 99%
“…Nakasato et al 23 reported a survival rate of 70% at 5 years for SCC. However, this rate decreases to 30.8% in the presence of metastases in the regional lymph area 24 .…”
Section: Palate Cancermentioning
confidence: 99%
“…Gingival SCC is relatively rare and represents < 10% of all oral cancers in the United States [14] , while gingival SCC is the second-most common oral cancer in Japan [15] . Surgical resection (marginal or segmental mandibulectomy) for SCC of the mandible is usually the preferred primary treatment because systemic chemotherapy is regarded as inadequate against a tumor with extensive bone destruction [16] . Despite clinical trials of various treatment strategies, prognosis and locoregional control remain poor in advanced cases of SCC in the mandible because involvement of the retromandibular trigone is more likely to be associated with multidirectional invasion [16] .…”
Section: Introductionmentioning
confidence: 99%